Mass balance of the Antarctic Ice Sheet from 1992 to 2017 - Shepherd, Andrew; Ivins, Erik; Rignot, Eric; Smith, Ben; van den Broeke, Michiel; Velicogna, Isabella; Whitehouse, Pippa; Briggs, Kate; Joughin, Ian; Krinner, Gerhard; Nowicki, Sophie; Payne, Tony; et al. (My University, 2018)
The Antarctic Ice Sheet is an important indicator of climate change and driver of sea-level rise. Here we combine satellite observations of its changing volume, flow and gravitational attraction with modelling of its surface mass balance to show that it lost 2,720 +/- 1,390 billion tonnes of ice between 1992 and 2017, which corresponds to an increase in mean sea level of 7.6 +/- 3.9 millimetres (errors are one standard deviation). Over this period, ocean-driven melting has caused rates of ice loss from West Antarctica to increase from 53 +/- 29 billion to 159 +/- 26 billion tonnes per year; ice-shelf collapse has increased the rate of ice loss from the Antarctic Peninsula from 7 +/- 13 billion to 33 +/- 16 billion tonnes per year. We find large variations in and among model estimates of surface mass balance and glacial isostatic adjustment for East Antarctica, with its average rate of mass gain over the period 1992-2017 (5 +/- 46 billion tonnes per year) being the least certain.
Keywords: Future sea level; Antarctic ice sheet; Iceberg